The Effect of Mango Juice (Mangifera Indica) and Long Ripening on the Quality Of Cow's Milk Curd - Selly Fildawati; Linda Advinda; Azwir Anhar (UNIVERSITAS NEGERI PADANG, 2017)
The curd is a traditional food Minangkabau in West Sumatra. This product is made from buffalo milk made with buffalo milk entering into the bamboo and covered with banana leaves and left at room temperature for about 1 to 2 days. Due to the limited availability of buffalo milk, buffalo milk is replaced with cow's milk. Obstacles encountered in the development of the curd is curd less flavorful savory and original taste sour curd so that the public interest is reduced. Therefore, we need a way to neutralize the smell and taste of sour curds, one of which is the juice of mango (Mangifera indica). The purpose of this study was to determine the effect of mango juice and long ripening on the quality of cow's milk curd. This study is experimental and descriptive. The design used was a 3x2 factorial randomized block design with three replications. A factor is the mango juice consisting of 3 treatment, and long ripening factor B is composed of 2 treatments. Research was conducted in January 2016 in the Laboratory of Livestock Product Technology Faculty of Animal UNAND. Parameters measured were total acid content, protein content, and organoleptic. Data were analyzed by descriptive qualitative analysis of variance (ANOVA) and a further test DNMRT at 5% level. The results of this study are the addition of mango juice and long curing does not affect the total acid content (% TAT). However, the addition of mango juice and long curing effect on protein levels although there is no interaction between the concentration and duration of ripening. Lowest total acid level was the control treatment on a long curing 48 hours and total acid concentration is the highest concentration of 3% at 36 hours. Lowest protein content that is the control treatment at 36 hours and the highest concentration of 3% at 48 hours. The results of organoleptic tests show the variation of each treatment. Keyword: cow's milk curd, mango juice, total acid content, protein content, organoleptic.